Oscillating Positive Airway Pressure Versus CPAP for the Treatment of Obstructive Sleep Apnea - Haba-Rubio, José; Petitpierre, Nicolas Julien; Cornette, Françoise; Tobback, Nadia; Vat, Sopharat; Giallourou, Theresia; Al-Jumaily, Ahmed; Heinzer, Raphael (Frontiers in Medicine, 2015)
Although continuous positive airway pressure (CPAP) is the most effective therapy for obstructive sleep apnea, it is not always well tolerated by the patients. Previous physiological studies showed that pressure oscillations applied to the pharynx could activate upper airway muscles, but it is not clear whether these pressure oscillations could be tolerated during sleep in obstructive sleep apnea (OSA) patients. The aim of this study was to assess the tolerance of O-PAP (a CPAP device delivering high-frequency pressure oscillations to the upper airway) compared to CPAP. 14 OSA patients currently on CPAP (age 59.9±10.1 y.o., BMI 34.8±7.2 kg/m2, initial AHI: 58.7±25.2 events/hour) used O-PAP or CPAP on two consecutive nights under polysomnography, in a single-blind randomized crossover design to assess sleep quality. A subtherapeutic pressure (70% of the optimal titrated pressure) was applied in both conditions and the residual apnea-hypopnea index (AHI) with each technique was also compared. There was no difference in measured or perceived sleep quality between the two treatment modalities (Sleep efficiency 90.0% vs 88.1%, p= 0.54). Despite the small sample, we also found a trend toward a decrease in residual respiratory events with O-PAP compared to CPAP (median AHI 14.3 vs 20.5/h, p=0.194). The good tolerance of O-PAP and the positive trend toward a reduction in residual AHI should stimulate further research on the effects of O-PAP in OSA patients.